2012
DOI: 10.1111/j.1751-9004.2011.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Psychosocial Factors for Diabetes Outcomes among Children with Type 1 Diabetes: A Review

Abstract: We adopt a risk and resistance framework to review the literature on the psychosocial factors that influence diabetes outcomes—specifically self‐care behavior (blood glucose monitoring, diet, exercise, insulin administration) and glycemic control. We examine both personal and social/environmental risk and resistance factors. We conclude by suggesting conceptual and methodological directions for future research. Conceptually, we suggest that researchers examine the synergy among variables that cut across domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 92 publications
(117 reference statements)
0
18
1
1
Order By: Relevance
“…Whereas anxious attachment and neediness draw from a fear of abandonment and needing approval of others which may elicit behaviours that contribute to interpersonal stressors, unmitigated communion draws from being overinvolved in caring for others to the exclusion of oneself. Whereas anxious attachment and neediness are vulnerability factors for depression, unmitigated communion is predictive of poor health outcomes Helgeson & Palladino, 2011). While Helgeson et al (2015) demonstrated that unmitigated communion was related to increased support giving and interpersonal problems such as being overly nurturant, intrusive, and exploitable, unmitigated communion was not associated with dependent interpersonal stress or independent stress in the present study.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Whereas anxious attachment and neediness draw from a fear of abandonment and needing approval of others which may elicit behaviours that contribute to interpersonal stressors, unmitigated communion draws from being overinvolved in caring for others to the exclusion of oneself. Whereas anxious attachment and neediness are vulnerability factors for depression, unmitigated communion is predictive of poor health outcomes Helgeson & Palladino, 2011). While Helgeson et al (2015) demonstrated that unmitigated communion was related to increased support giving and interpersonal problems such as being overly nurturant, intrusive, and exploitable, unmitigated communion was not associated with dependent interpersonal stress or independent stress in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Whereas anxious attachment and neediness are vulnerability factors for depression, unmitigated communion is predictive of poor health outcomes Helgeson & Palladino, 2011). Whereas anxious attachment and neediness draw from a fear of abandonment and needing approval of others which may elicit behaviours that contribute to interpersonal stressors, unmitigated communion draws from being overinvolved in caring for others to the exclusion of oneself.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the factors identified were consistent with previous studies that analysed average HbA 1c levels and included older age, female gender, ethnic minority status, longer diabetes duration, lower glucose monitoring frequency, fewer or missed clinical appointments, and insulin delivery via injection versus insulin pump as associated with poorer HbA 1c trajectories. Associations with several family environment and psychosocial variables reported in cross‐sectional studies were also demonstrated in the longitudinal trajectory studies. However, we also noticed that 4 studies reported nonsignificant associations of poor HbA 1c trajectories and some of the variables mentioned above including age, gender, ethnicity, disease duration, clinical appointment, insulin treatment, and self‐control, although the direction of association effect was consistent with other studies.…”
Section: Discussionmentioning
confidence: 53%
“…Relatively little is known about the specific distribution of trajectories of glycemic control among early adolescents with type 1 diabetes and the factors that predict them. Most studies have focused on description and prediction of average levels of glycemic control, often over limited periods (e.g., one year) (Butler et al, 2008; Drotar et al, 2013; Helgeson & Palladino, 2012; Ingerski, Anderson, Dolan, & Hood, 2010). …”
mentioning
confidence: 99%